PENGEMBANGAN PERGURUAN TINGGI ISLAM DI INDONESIA - Lewis, Azizul Mahdha; Khotima, Husnul; Abdurrahmansyah, Abdurrahmansyah; Handayani, Tutut (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This article aims to discuss the development of Islamic higher education in Indonesia. This research uses a qualitative descriptive approach and method, systematic analysis of theories and regulations that are directly related to the research title Development of Islamic higher education in Indonesia, through a library research method approach. After collecting various books and journals related to the discussion, then analyzing the material through literature study with the results of the analysis in descriptive form. The development of Islamic higher education in Indonesia lies in the transformation of Islamic higher education which can be divided into three phases of development, namely: first, in the form of high schools including the types of higher education: Islamic High School (STI), State Islamic Religious College (PTAIN), Academy Department of Religious Sciences (ADIA) and there is a State Islamic Religious College (STAIN). In this phase, the scientific group developed an Islamic scientific discipline. The second group continues, namely a form of institute where scientific development is more widespread, this institution is called the State Islamic Religious Institute (IAIN). This institution has developed a group of similar sciences which include Islamic religious sciences, but often as time goes by there is not only one science. And then the third group, is in the form of universities (UIN).